Effect of PBT molecular weight and reactive compatibilization on the dispersed-phase coalescence of PBT/SAN blends - Ito, Edson Noriyuki (2010)
Poly(butylene terephthalate) (PBT)/styrene-acrylonitrile copolymer (SAN) blends were investigated with respect to their phase morphology. The SAN component was kept as dispersed phase and PBT as matrix phase and the PBT/SAN viscosity ratio was changed by using different PBT molecular weights. PBT/SAN blends were also compatibilized by adding methyl methacrylate-co-glycidyl methacrylate-co-ethyl acrylate terpolymer, MGE, which is an in situ reactive compatibilizer for melt blending. In noncompatibilized blends, the dispersed phase particle size increased with SAN concentration due to coalescence effects. Static coalescence experiments showed evidence of greater coalescence in blends with higher viscosity ratios. For noncompatibilized PBT/SAN/MGE blends with high molecular weight PBT as matrix phase, the average particle size of SAN phase does not depend on the SAN concentration in the blends. However noncompatibilized blends with low molecular weight PBT showed a significant increase in SAN particle size with the SAN concentration. The effect of MGE epoxy content and MGE molecular weight on the morphology of the PBT/SAN blend was also investigated. As the MGE epoxy content increased, the average particle size of SAN initially decreased with both high and low molecular weight PBT phase, thereafter leveling off with a critical content of epoxy groups in the blend. This critical content was higher in the blends containing low molecular weight PBT than in those with high molecular weight PBT. At a fixed MGE epoxy content, a decrease in MGE molecular weight yielded PBT/SAN blends with dispersed nanoparticles with an average size of about 40 nm